Qualifiers in English and Vietnamese nominal groups - a systemic functional comparison. M.A. Thesis Linguistics: 60 22 15 - Bùi, Thị Huyền (University of Languages and International Studies, 2017)
Functional grammar is a complex and comprehensive model, and among many schools of grammar such as traditional grammar, structural grammar, and transformational generative gramamr, it is considered by many linguists as the least popular but the most challenging. Nominal groups and its parts were studied by some Vietnamese researchers